Design and Implementation of a Didactic Test Bench Based on PLC s7-1200 - BOUDELAA Lina; BENMOUSSA Mohammed Taher; HADJAISSA Aboubakeur (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
Our project aims to design and implement a practical learning tool (didactic test bench) using a PLC (Programmable Logic Controller). This didactic tool benefits students of automation, instrumentation, and embedded systems to experiment their practical works as it provides hands-on experience alongside the theoretical knowledge. This project go through three stages, the first stage involved the selection and gathering of all components used to build our practical didactic tool, followed by the design and implementation in the second stage, finally, the last stage is devoted to the testing and validation through two experiments: Speed control of a DC motor based on PI controller and water level control based ON/OFF controller.
SPECIALTY: Automation & Industrial Computing